Necroptosis, unlike pyroptosis mediates right ventricular damage in pulmonary arterial hypertension. (10th June 2022) - Jarabicova, I; Horvath, C; Velasova, E; Bies Pivackova, L; Veteskova, J; Klimas, J; Krenek, P; Adameova, A
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Scientific Grant Agency of the Ministry of Education, Science, Research and Sport of the Slovak Republic The Slovak Research and Development Agency Introduction: Necroptosis has been found to underlie myocardial damage in various pathological states, however its role as well as its potential interconnection to another cell damaging processes under conditions of pulmonary arterial hypertension (PAH) remains insufficiently understood. Purpose: In view of these facts, we aimed to investigate the signalling of both necroptosis and pyroptosis in the lung and right ventricular (RV) tissue affected by PAH and we also examined the circulating levels of receptor-interacting protein kinase 3 (RIP3). Methods: Male Wistar rats were administrated either vehicle (Control group) or monocrotaline (MCT) (60 mg/kg, s. c.) to induce PAH. The MCT-treated animals were sacrificed 4 weeks after the treatment (MCT group) or prematurely, based on rapid health deterioration, thereby indicating the advanced stage of PAH (ptMCT group). Pulse oximetry, gravimetry and evaluation of myocardial damage markers were used to assess the development of PAH. The molecular analyses (ELISA, RT-qPCR and immunoblotting) were used to examine the potential underlying mechanisms of tissue damage due to cell death. Results: In the RVs, the expression of both pThr231/Ser232-RIP3 and pSer345-mixed linkage kinase domain-like protein was elevated equally in both PAH stages, strongly indicating promotion of necroptosis. Contrary in the lungs affected by PAH, the upregulation of pThr231/Ser232-RIP3 likely proceeded to pyroptotic rather than necroptotic cell death activation, as evidenced by caspase-1 and N-terminal gasdermin D increase. Moreover, we found that the plasma RIP3 levels increased with the severity of PAH stage and positively correlated with RV hypertrophy, but not with cardiac hemodynamic stress markers. Conclusions: In summary, we showed for the first time that PAH-induced damage of RV and lung tissue might be mediated by different necrosis-like cell death forms with a crucial role pThr231/Ser232-RIP3. Furthermore, we suggested that the plasma RIP3 might serve as an additional diagnostic and prognostic marker of cardiac damage due to PAH.